Non–Vitamin K Antagonist Oral Anticoagulants in Coronary Artery Disease - Al Said, Samer; Ellscheid, Michael; Beltsios, Eleftherios T.; Frey, Norbert (Hämostaseologie, 2021)
The prevention of atherothrombotic events is the primary goal in the treatment of patients with arteriosclerotic disorders. Despite recent improvements in the management of coronary artery disease (CAD) with revascularization techniques and antiplatelet therapy, some patients remain at risk of recurrent cardiovascular events. This could be related to additional thrombin generation. As a result, there has been interest in developing novel therapies to prevent thromboembolic events, targeting thrombin-mediated pathways. These include non–vitamin K antagonist oral anticoagulants (NOACs). This article aims to summarize the recent clinical studies that investigated the role of NOACs in CAD.
Keywords: coronary artery disease; non–vitamin K antagonist; oral anticoagulants; direct antithrombin agents; atherosclerosis